Performance of vetiver grass (Vetiveria zizanioides) for phytoremediation of contaminated water - Syed Hasan, Sharifah Nur Munirah; Mohd Kusin, Faradiella; Lim, Ashton Sue Lee; Sharif @ Ukang, Tony Austin; Mohamat Yusuff, Ferdius @ Ferdaus; Zaiton Ibrahim, Zelina (EDP Sciences, 2016)
In tolerance towards metal uptake, there is a need to evaluate the performance of vetiver grass for metal removal to reduce water impurity. This study was aimed to evaluate contaminant removal by vetiver grass at varying root length and plant density and determine the metal uptake in vetiver plant biomass. Pollutant uptake of vetiver grass was conducted in laboratory experiment and heavy metal analysis was done using acid digestion and Atomic Absorption Spectrometry. Findings indicated that the removal of heavy metal was decreased in seven days of the experiment where iron shows the highest percentage (96%; 0.42 ppm) of removal due to iron is highly required for growth of vetiver grass. Removal rate of heavy metals in water by vetiver grass is ranked in the order of Fe>Zn>Pb>Mn>Cu. Results also demonstrated greater removal of heavy metals (Cu, Fe, Mn, Pb, Zn) at greater root length and higher density of vetiver grass because it increased the surface area for metal absorption by plant root into vetiver plant from contaminated water. However, findings indicated that accumulation of heavy metals in plant biomass was higher in vetiver shoot than in root due to metal translocation from root to the shoot. Therefore, the findings have shown effective performance of vetiver grass for metal removal in the phytoremediation of contaminated water.